The Role of The Corona Epidemic in Some Developments of Behavioral Patterns and Social Habits in Individuals from The Point of View of The Faculty Teaching Staff of The University - Karwan Mahmoud Mustafa Hassan; Rasheed MullaHussein Ahmed Al-Barwari (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
This study aims to find out the role of the Corona epidemic in some developments of behavioral patterns and social habits in individuals from the point of view of the faculty teaching staff of the university. The researchers used this descriptive curriculum, and the study community is represented by faculty Teaching staff at Salahaddin University, where the sample of the study (266) was a Teaching staff. The researchers used used the measure of the role of the Corona epidemic in some developments of behavioral patterns and social habits. The results showed that the Corona epidemic has a role in some developments of behavioral patterns and social habits among the faculty Teaching staff of the university, and there are significant differences in the views of the faculty Teaching staff of the university about the role of the emerging Corona epidemic in some developments of behavioral patterns and social habits in individuals from the point of view of the faculty Teaching staff of the university according to the sex (male-female), and the absence of statistically significant differences in some developments of behavioral patterns according to variables (age, specialization, years of experience, scientific title), The results also indicated that there were statistically significant differences in some developments of social habits according to variables (specialization, years of experience, scientific title), and the results indicated statistically significant differences in some developments of social habits according to the variable (age) and in favor of the age group (58-67). In the light of the results, a number of conclusions and recommendations have been submitted.